Study and Effect of Ignition Timing on the Combustion Characteristics of Gasoline En 91 in a Spark Ignition Engine - Joseph Lungu; Lennox Siwale; Edwin Luwaya (New Approaches in Engineering Research Vol. 1, 2021)
The purpose of this work was to show and elucidate the combustion characteristics of gasoline EN91 in a spark ignition engine under different ignition timing. The combustion characteristics of gasoline under different ignition timing were obtained using the kiva4 code. The numerical results obtained in kiva4 were compared with the numerical results from other researchers who used kiva3vr2 as the simulation code. For achieving this, two cases were investigated; a complete engine cycle was successfully simulated using a four valve pent - roof engine and a comparison was made with experimental results by other researchers. At a constant speed of 600 rpm, a BASF (BadischeAnilin- und Soda Fabrik) octane rating engine - single cylinder was used where ignition timing was changed in the range of 40 BTDC to 180 BTDC. The temperature and pressure combustion characteristics in kiva4 and kiva3vr2 show a percentage error of 10%. The peak and average temperature and pressure under different ignition timing from the Kiva4 code and measured experimental results shows a qualitative closeness with a percentage error of 4%. The average temperature and pressure in kiva4 were 640K and 16.48 bar while in kiva3vr2 were 600K and 14.83 bar, the peak temperature and pressure in kiva4 were 2316.3K and 21.5 bar while in kiva3vr2 were 2171.5K and 19.4 bar. The peak temperature and pressure in kiva4 at 40 BTDC was 2075.7K and 20.37 bar while at 180 BTDC was 2166.0K and 23.47bar. The peak temperature and pressure increase with increasing spark advance until the most favorable instant time is determined. Best performance was achieved when the ignition time was set to10 degrees before top dead center.